Effect of resveratrol on alcohol-induced mortality and liver lesions in mice - Bujanda, Luis (BioMed Central, 2006)
BACKGROUND: Resveratrol is a polyphenol with important antiinflammatory and antioxidant properties. We investigated the effect of resveratrol on alcohol-induced mortality and liver lesions in mice. METHODS: Mice were randomly distributed into four groups (control, resveratrol-treated control, alcohol and resveratrol-treated alcohol). Chronic alcohol intoxication was induced by progressively administering alcohol in drinking water up to 40% v/v. The mice administered resveratrol received 10 mg/ml in drinking water. The animals had free access to standard diet. Blood levels were determined for transaminases, IL-1 and TNF-α. A histological evaluation was made of liver damage, and survival among the animals was recorded. RESULTS: Transaminase concentration was significantly higher in the alcohol group than in the rest of the groups (p < 0.05). IL-1 levels were significantly reduced in the alcohol plus resveratrol group compared with the alcohol group (p < 0.05). TNF-α was not detected in any group. Histologically, the liver lesions were more severe in the alcohol group, though no significant differences between groups were observed. Mortality in the alcohol group was 78% in the seventh week, versus 22% in the alcohol plus resveratrol group (p < 0.001). All mice in the alcohol group died before the ninth week. CONCLUSION: The results obtained suggest that resveratrol reduces mortality and liver damage in mice.